Journey of a Thousand Miles : An Extraordinary Life (Book collections on Project MUSE., 2017)
"Born into poverty in Japanese-occupied Taiwan, Ruey Yu overcame near-starvation during the Second World War. Destiny, however, had other plans for him: he was to become an award-winning biochemist, then the co-founder of what would soon become the multi-million-dollar skin care company NeoStrata. After living through the Second World War and the post-war military dictatorship of General Chiang Kai-Shek, Dr. Yu won a coveted post-graduate scholarship to study chemistry at the University of Ottawa. He subsequently took up a research position at the renowned Skin and Cancer Hospital (Temple University) in Philadelphia, where he collaborated with pre-eminent dermatologist Dr. Eugene Van Scott to develop treatments for serious skin diseases. In 1972, Dr. Yu and Dr. Van Scott discovered that fruit acids, known as AHAs, could effectively treat the disfiguring skin disease ichthyosis, changing the lives of thousands of people who suffered from this debilitating illness. Their further research into the biochemical properties of AHAs led to the discovery of the anti-wrinkle and anti-aging effects of these natural substances--a discovery that was licensed by skin care companies around the world, sparking the multibillion- dollar cosmeceutical industry."--